Influence of Baseline Diastolic Blood Pressure on Effects of Intensive Compared With Standard Blood Pressure Control. Issue 2 (9th January 2018) - Beddhu, Srinivasan; Chertow, Glenn M.; Cheung, Alfred K.; Cushman, William C.; Rahman, Mahboob; Greene, Tom; Wei, Guo; Campbell, Ruth C.; Conroy, Margaret; Freedman, Barry I.; Haley, William; Horwitz, Edward; et al.
Abstract : Background: In individuals with a low diastolic blood pressure (DBP), the potential benefits or risks of intensive systolic blood pressure (SBP) lowering are unclear. Methods: SPRINT (Systolic Blood Pressure Intervention Trial) was a randomized controlled trial that compared the effects of intensive (target <120 mm Hg) and standard (target <140 mm Hg) SBP control in 9361 older adults with high blood pressure at increased risk of cardiovascular disease. The primary outcome was a composite of cardiovascular disease events. All-cause death and incident chronic kidney disease were secondary outcomes. This post hoc analysis examined whether the effects of the SBP intervention differed by baseline DBP. Results: Mean baseline SBP and DBP were 139.7±15.6 and 78.1±11.9 mm Hg, respectively. Regardless of the randomized treatment, baseline DBP had a U-shaped association with the hazard of the primary cardiovascular disease outcome. However, the effects of the intensive SBP intervention on the primary outcome were not influenced by baseline DBP level ( P for interaction=0.83). The primary outcome hazard ratio for intensive versus standard treatment was 0.78 (95% confidence interval, 0.57–1.07) in the lowest DBP quintile (mean baseline DBP, 61±5 mm Hg) and 0.74 (95% confidence interval, 0.61–0.90) in the upper 4 DBP quintiles (mean baseline DBP, 82±9 mm Hg), with an interaction P value of 0.78. Results were similar for all-cause death and kidney events. Conclusions: Low baseline DBP was associated with increased risk of cardiovascular disease events, but there was no evidence that the benefit of the intensive SBP lowering differed by baseline DBP. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01206062. Abstract : Supplemental Digital Content is available in the text.